Effect of Post-fermentation Maceration on the Chemical Composition of Some Wines - Nino G. Vephkhishvili; Marine G. Bezhuashvili; Vano L. Shiukashvili (New Innovations in Chemistry and Biochemistry Vol. 4, 2021)
The therapeutic and preventive value of red wine treatment is highly dependent on the presence of various groups of phenolic compounds. In this sense, the post-fermentative maceration method was used to make phenol-rich Saperavi and Cabernet Sauvignon wines. It was determined that the following changes occurred during the post-fermentation maceration process: total phenols, oligomeric proanthocyanidins, common stains, trans-resveratrol, \(ε\)-viniferin, alcohol, volatile acidity, acidity titer and changes in the amount of extracts. The best post-fermentation maceration parameters for the investigation of these wines were determined as a consequence of the experiment. Tightness, duration 15 days, temperature - + 25 - + 27\(^°\)C.